Interfacial Reactions between Lithium and Grain Boundaries from Anatase TiO2–TUD‑1 Electrodes in Lithium-Ion Batteries with Enhanced Capacity Retention - Ballestas-Barrientos, Alfonso R; Xia, Qingbo; Masters, Anthony F; Ling, Chris D; Maschmeyer, Thomas (ACS omega, 2020)
The synergistic incorporation of anatase TiO2 domains into siliceous TUD-1 was optimized in this work and the resulting sample was implemented as the electrode in lithium-ion batteries. Triethanolamine was used as both the templating and complexing agent, the Si/Ti ratio was controlled, and the formation of Ti–O–Si bridges was optimized, as revealed through Fourier transform infrared spectroscopy, with the porous character of the materials being confirmed with N2 adsorption–desorption isotherms. The controlled formation of Ti–O–Si bridges resulted in attractive specific charge capacities, high rate capability, and a good retention of capacity. The electrochemical performance of the composite material clearly demonstrates a synergistic effect between pure TiO2 in its anatase form and the otherwise inactive siliceous TUD-1 matrix. Specific capacities of 300 mA h g–1 with a retention of 94% were obtained at a current density of 0.1 A g–1 over 100 cycles. This work showcases the use of bifunctional templating agents in the improvement of the performance and the long-term cyclability of composite electrodes, which can be potentially applied in future synthesis of energy materials.